Biochemistry - Armstrong, Frank Bradley (Oxford University Press, 1989)
Popular for its accessibility and comprehensiveness, Armstrong's "Biochemistry" is highly regarded as a textbook for short introductory courses on biochemistry. Its clear writing and careful organization acommodates the needs of students from a variety of disciplines including biology, zoology, botany, other life sciences and agriculture. The text focuses on fundamental principles of biochemistry, using physiological examples and experimental results to clarify and reinforce concepts. The third edition has been completely revised to encompass major advances and two new chapters have been added on recombinant DNA research and the immune system. Of the 521 illustrations, several are completely new for this edition, including some drawings by Irving Geis of gene transcription, translation and protein synthesis.